An Annotated List of the Vascular Plants of the Projected Landscape Reserve «Lesovyy Canyon» (Kherson Region, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The list of the vascular plants of the projected landscape reserve «Lesovyy Canyon» includes 222 species of 155 genera, 52 families, 3 classis, 2 divisio. Among them 13 species included to the various Red Lists.
Keywords: flora, vascular plants, landscape reserve «Lesovyy Canyon», an annotated list.